اثر الاختلاف في شرح المتون الاصولية - شكري فارس ياسين; د/ قبلي بن هني (جامعة عمار ثليجي الاغواط, 2024)
مـستخلص البحث يُوجّههذاالبحثالقارئإلىالاطلاععلىمختلفالتخريجاتالفقهيةلدلالةالأمر،باعتبارهأساسالخطابالشرعي ، والمصدر الأول للأحكام التكليفية التي بدورها تتوقف عليه . وتهدف هذه الدراسة إلى الكشف عن طبيعة الخلاف الأصولي في دلالة الأمر وبيان حقيقته اللفظية والمعنوية ، وما من شأنه أن ينتج عن هذا الخلاف من الآثار في الأحكام العملية . كما يبين أن اختلاف الفقهاء في الجملة لم يكن اختلافا محرما ولا مذموما ، لكونه يرجع إلى أسباب علمية موضوعية ، تتعلق بالاختلاف في القواعد الأصولية عموما ، والاختلاف في قواعد باب الأمر بوجه خاص . The summing up This research directs the reader to review the variousjurisprudential interpretations of the meaning of the matter, as it is the cornerstone and basis of the legal discourse, and the primary source of the obligatory rulings that in turn depend on it. This study aims to reveal the nature of the fundamentalist disagreement regarding the meaning of the matter and explain its verbal and moral truth, and the effects that this disagreement would have on practical rulings. It also shows that the disagreement of the jurists in the sentence was neither forbidden nor reprehensible, because it was due to objective scientific reasons, related to the difference in the fundamental rules in general, and the difference in the rules of the matter section in particular.
باب الامر من الورقات انموذجا